2019
DOI: 10.1002/rmv.2055
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of phages, bacteria, and the human immune system: Evolutionary changes in phage therapy

Abstract: Summary Phages and bacteria are known to undergo dynamic and co‐evolutionary arms race interactions in order to survive. Recent advances from in vitro and in vivo studies have improved our understanding of the complex interactions between phages, bacteria, and the human immune system. This insight is essential for the development of phage therapy to battle the growing problems of antibiotic resistance. It is also pivotal to prevent the development of phage‐resistance during the implementation of phage therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 157 publications
(341 reference statements)
0
22
0
1
Order By: Relevance
“…Bacteriophages (or simply phages) are viruses that exclusively infect bacteria. Interactions between bacteriophages and human or animal organisms play an important role in phage therapy research [2][3][4]. Potential applications of bacteriophages in medicine, as well as general studies of microbiomes in animals and humans, have induced a need for developing tools that facilitate studies of phage circulation and deposition in tissues and cells.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriophages (or simply phages) are viruses that exclusively infect bacteria. Interactions between bacteriophages and human or animal organisms play an important role in phage therapy research [2][3][4]. Potential applications of bacteriophages in medicine, as well as general studies of microbiomes in animals and humans, have induced a need for developing tools that facilitate studies of phage circulation and deposition in tissues and cells.…”
Section: Introductionmentioning
confidence: 99%
“…In all strains except GU01, the pronounced bacteriolysis induced by the phage was followed by a small increase in turbidity and a subsequent further decrease. It is not clear whether this pattern reflects an "evolutionary arms race" between the phage and host bacterium (25), but no substantial regrowth of any of the bacterial strains was apparent for up to 24 h after the onset of culture. Together, these results suggested that ⌽EF24C-P2 might be effective for the treatment of E. faecalis infection regardless of the VAN sensitivity of the bacterium.…”
Section: Resultsmentioning
confidence: 99%
“…(VRE) have been described (5)(6)(7)(8)(9)(10)(11)(12). Infection with E. faecalis was found to account for 16% of postoperative endophthalmitis cases in Japan, 25.4% in South Korea, and 31.1% in Sweden (13)(14)(15). The development of alternatives to antibiotics for the treatment of drug-resistant E. faecalis infection is therefore urgently needed.…”
mentioning
confidence: 99%
“…For example, Yu and colleagues designed cocktails with ‘guard’ phage that inhibit the evolution of phage resistance because they were previously experimentally evolved to infect likely‐to‐evolve resistant cells (Yu et al ., 2018). However, many researchers have described multiple rounds of phage‐host coevolution suggesting that protection by guard phage may be temporary on an evolutionary time scale, although this has not been tested (Koskella and Brockhurst, 2014; Jariah and Hakim, 2019). Others have used molecular techniques to identify phage binding sites and subsequently design cocktails that use multiple binding sites to increase both the number of mutations required for resistance and the cost of resistance (Filippov et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%